Processos de estigmatização e de enfrentamento à violência conjugal vivenciado por mulheres - Xavier, Natacha Farias (2019)
Violence against women in Brazil has proven to be an issue that requires special attention because it is a complex and multifaceted phenomenon. According to the 2015 Map of Violence (BRAZIL, 2015), in a group of 83 countries, Brazil ranks 5th in violence against women. The Northeast is one of the regions with the highest rates of increase over a period of ten years, there was a growth of 79.3%, and in Ceará a rate of 6.3 homicides per 100,000 women is identified, which is higher than the national average rate of 4.6 homicides per 100,000 women, with the city of Fortaleza occupying the 4th position among the cities with the highest rate of feminicide in the country. To guarantee protection and to break with the cycle of conjugal violence, some women appeal to the Justice, through the Law Maria da Penha, however, there are women that after the denunciation and arrest of the aggressor, they communicate their desire to live again with them. Thus, how do the processes of stigmatization and confrontation with marital violence experienced by women who have returned to the affective relationship with their aggressors occur? Therefore, the general objective is to understand the processes of stigmatization and confrontation with marital violence experienced by women, who have returned to the affective relationship with their aggressors. The methodology is qualitative in nature, using the technique of narrative interview. Five women victims of marital violence were interviewed and assisted at the Center for Assistance to the Families of Persons Deprived of Liberty - NUASF, of the Special Coordination of the Prison System - COESP. For data analysis, the material obtained was analyzed through Bardin's Content Analysis with the help of the software ATLAS.ti 5.2. As a result, it was noticed that there is a close relationship between violence and stigma, when women affirm their desire to maintain a socio-affective relationship with their aggressors. Thus, it is frequent to observe that women who find themselves in this situation tend to have a life traversed by feelings such as shame, humiliation and guilt / blame for violence, categories that express psychological suffering and reverberate in reducing their cycle of social support and increasing the production of stigma. On the other hand, when these women have a support network that aims to promote protection against violence and stigma, social support becomes a powerful category. In this sense, the narratives that are lives crossed by machismo, affective dependence and female social roles have a strong appeal for the maintenance of the man-woman relationship. The categories of oppression produce the social stigma that women who return to affective coexistence with their aggressors 'like to be beaten'. For the confrontation, a transitional support network was identified, which organizes itself according to the needs and feelings of acceptance in the group and contributes to a path of empowerment, when women are offered spaces for speech and awareness.